Tradycja kontra nowoczesność jako element konkurencyjności obszarów wiejskich - Woźniak, Marian (Tradition Versus Modernity as an Element of Competitiveness of the Rural Areas, 2006)
The bigger interest in rural issues, which become the gist of the dispute about Poland's place in the United Europe, has been observed since the 1990s. The question about rural areas in the opinion of Polish society becomes essential, as well as about countryside, its culture and landscape. The article discusses the problem of rural areas competitiveness, based on the countryside notion as the place of agricultural production and attractive cultural landscape.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 523-528